2017
DOI: 10.1016/j.ceramint.2016.11.178
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behaviour of multilayer and functionally-graded YSZ/Gd2Zr2O7 coatings

Abstract: Zirconates with pyrochlore structure, such as Gd2Zr2O7, are new promising thermal barrier coatings because of their very low thermal conductivity and good chemical resistance against molten salts. However, their coefficient of thermal expansion is low, therefore their thermal fatigue resistance is compromised. As a solution, the combination of yttria-stabilised zirconia (YSZ) and Gd2Zr2O7 can reduce the thermal contraction mismatch between the thermal barrier coating parts.In the present study, two possible de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Gd 2 Zr 2 O 7 phase was maintained its stable position after APS process. Carpio et al [23] showed that YSZ-and GZ-based TBCs had the same porosity value when State of the Art of Gadolinium Zirconate Based Thermal Barrier Coatings: Design, Processing… DOI: http://dx.doi.org/10.5772/intechopen.85451 the same APS parameters were used. These results indicate that there is no microstructural problem in producing GZ by APS.…”
Section: Coating Process and Coating Architectures 21 Production Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Gd 2 Zr 2 O 7 phase was maintained its stable position after APS process. Carpio et al [23] showed that YSZ-and GZ-based TBCs had the same porosity value when State of the Art of Gadolinium Zirconate Based Thermal Barrier Coatings: Design, Processing… DOI: http://dx.doi.org/10.5772/intechopen.85451 the same APS parameters were used. These results indicate that there is no microstructural problem in producing GZ by APS.…”
Section: Coating Process and Coating Architectures 21 Production Of mentioning
confidence: 99%
“…However, besides all of these advantages, GZ has two poor properties affecting its thermal cycling (TC) behavior in a negative manner. One of them is its low coefficient of thermal expansion (CTE, 10.4 × 10 −6 K −1 and 11 × 10 −6 K −1 for GZ and YSZ, respectively), and another one is its high tendency to react with the TGO layer [8,9,13,14,19,[21][22][23][24][25][26][27][28][29][30][31][32]. These problems were solved by using multilayered (MLed) and functionally graded (FGed) designs.…”
mentioning
confidence: 99%
“…Two main methods are usually used for manufacturing TBCs top coat, namely: Atmospheric Plasma Spray (APS), and Electron Beam Physical Vapor Deposition (EB-PVD) [15].Other new methods include suspension plasma spray [16] solution precursor plasma spray [17], plasma spray-physical vapor deposition [18] and electrophoretic deposition [19]. Recently, advanced TBCs such as nanostructured TBCs [20] and functionally graded TBCs [21] with enhanced performance were produced. TBC performance can also be enhanced by laser glazing [ 22].…”
Section: Introductionmentioning
confidence: 99%
“…Analytical modeling of the dynamic thermal response of materials with gradation of thermal properties in the direction perpendicular to the surface is of interest in various fields. This is an essential step in the design and optimization of the structure of functionally graded materials, such as those intended to withstand high thermal loads (e.g., thermal barriers) [1], [2], [3]. This may also be useful for interpreting the thermal response of functionally graded materials designed for other purposes, such as achieving a specific mechanical property (e.g., hardness).…”
Section: Introductionmentioning
confidence: 99%